Missing point on the corner by using extension cases of advancing front mesh method - Awang, Noorehan; O. K. Rahmat, Rahmita Wirza; Ng, Seng Beng; Jaafar, Azmi; Sulaiman, Puteri Suhaiza; Ilias, Mohd Rijal (World Academy of Research in Science and Engineering, 2020)
Surface reconstruction was mainly the important process in reverse engineering. However undesirable holes often exist due to accessibility limitation on scanners. To bridge the gap, the paper proposes an enhanced algorithm of filling holes for 3D objects based on Advancing Front Mesh (AFM) method. The holes focused was on the missing point on the corner of the object. In the algorithm, object was chosen and two procedure used to achieved the results. The procedure consists of two steps namely hole detection and hole filling. The experiment demonstrates the result of hole filling can recover the original shape of the hole region precisely and effectively.